PENGARUH BEBAN TERHADAP PREDIKSI UMUR FATIK DUDUKAN (BRACKET) AC OUTDOOR MENGGUNAKAN METODE ELEMEN HINGGA - LASINTA ARI NENDRA WIBAWA (Universitas Muria Kudus, 2020)
The study examines the effect of the load on fatigue life prediction of an outdoor AC bracket using the finite element method. Outdoor AC bracket design uses Autodesk Inventor Professional 2017, while finite element analysis uses Ansys Workbench. The outdoor AC bracket is subjected to a load of 20, 25, 30, and 35 kg with a fully-reserved type of loading. Gerber's mean stress theory is used to predict fatigue life. The outdoor AC bracket material uses Aluminum alloy 5052. The simulation results show that the outdoor AC bracket has a minimum fatigue life for loads of 20, 25, 30, and 35 kg, respectively is 1 x 108, 1.49 x 107, 1.93 x 106, and 6.64 x 105 cycles. Whereas the safety factor for minimum fatigue life for loads of 20, 25, 30, and 35 kg is 1.65; 1.32; 1.10; and 0.58. It shows the outdoor AC bracket can withstand the fatigue life of up to a minimum of 106 cycles for loads of 20, 25, and 30 kg because it has a safety factor of more than 1. While the 35 kg load of outdoor AC bracket fails to reach a minimum fatigue life of 106 cycles due to fatigue life prediction is only reached 6.64 x 105 cycles with a safety factor of less than 1, which is 0.58.